Understanding the mental health needs of Scotland's prison population: a health needs assessment - Gilling McIntosh, Lindsey; Rees, Cheryl; Kelly, Caroline; Howitt, Sheila; Thomson, Lindsay D. G. (Frontiers in Psychiatry, 2023)
Introduction This study reports on an assessment of mental health needs among Scotland's prison population which aimed to describe the scale and nature of need as well as identify opportunities to improve upon the services available. The project was commissioned by the Scottish Government to ensure that future changes to the services available to support the mental health and wellbeing of people in prison would be evidence-based and person-centered. Methods A standardized approach to health needs assessments was employed. The study was comprised of four phases. In phase I a rapid literature review was undertaken to gather evidence on the prevalence of mental health needs experienced by people in prison in the UK. In Phase II a multi-method and multi-informant national mapping exercise involving providers to all Scottish prisons was undertaken to describe the mental health services available, and any gaps in these services, for people in and leaving prison. In Phase III prevalence estimates of several mental health needs were derived for Scotland's current prison population, modeled from a national survey dataset of Scotland's community population using logistic regression. Finally in Phase IV, professional stakeholders and individuals with lived experience were interviewed to understand their experiences and insights on challenges to supporting the mental health and wellbeing of people in prison, and ideas on how these challenges could be overcome. Results Evidence across the four phases of this needs assessment converged indicating that existing provision to support the mental health of people in prison in Scotland was considered inadequate to meet these needs. Barriers to effective partnership working for justice, health, social work and third sector providers appear to have led to inadequate and fragmented care, leaving prisoners without the support they need during and immediately following imprisonment. Conclusions Joint and coordinated action from justice, health and social care, and third sector providers is needed to overcome enduring and structural challenges to supporting the mental health of people in prison. Eighteen evidence-based recommendations were proposed to the Scottish Government relating to the high-level and operational-level changes required to adequately meet the prison population's mental health needs.